(3MGTjI Ydi TQM GdYbGFO GdfSajIs - (3GdNjGdj, CMeO Hf ehSi, J (B862 (3g`s ((3eMeO hLjg GdOjfs)
(3ChdgG (B:s
(3HYO GdHSedI ; CeG HYO GdMeO deSJGgdg cJGH ajg fhQ hgOi ddfGS jQTOc Edi GdecGef GdNajI ef TQM GdYbGjO GdfSajIs
(3BNQgG (B:s
(3hHg jXgQ Cf gPG GdhLg CjVG jbjO JaVdge abW hCf GdaVd HjO Gddg jDJjg ef jTGA hGddg Ph GdaVd GdYXjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 262s
(3eYLe GdeDdajf (B1 / 315s
(3cTa GdXfhf (B2 / 1145s
(3T (B7 / 343s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds